Efficacy and safety of lacosamide as first add-on or later adjunctive treatment for uncontrolled partial-onset seizures: A multicentre open-label trial. (September 2015) - Zadeh, Wendy Waldman; Escartin, Antonio; Byrnes, William; Tennigkeit, Frank; Borghs, Simon; Li, Ting; Dedeken, Peter; De Backer, Marc; ,
Highlights: Lacosamide 300–400 mg/day was efficacious as a first or later add-on for POS. 37.5% of patients taking lacosamide as first add-on were seizure-free at 12 weeks. 14.9% of patients taking lacosamide as later add-on were seizure-free at 12 weeks. Both patient groups reported improvements from Baseline in quality of life outcomes. Lacosamide was well tolerated, with a good tolerability profile as a first add-on. Abstract: Purpose: To evaluate the efficacy and safety of lacosamide administered as either first add-on or later add-on antiepileptic drug (AED) therapy for patients with uncontrolled partial-onset seizures (POS). Methods: In this open-label, multicentre trial, patients with POS initiated oral lacosamide (titrated to 400 mg/day) either as add-on to first AED monotherapy, or as later add-on to 1–3 concomitant AEDs after ≥2 previous AEDs. The primary efficacy variable was the proportion of patients achieving seizure freedom for the first 12 weeks of the 24-week Maintenance Phase. Results: 456 patients received ≥1 dose of lacosamide (96 as first add-on, 360 as later add-on). In the first add-on cohort, 27/72 (37.5%) patients completed 12 weeks treatment and remained seizure-free; 18/68 (26.5%) remained seizure-free after 24 weeks. 64/91 (70.3%) patients achieved ≥50% reduction in seizure frequency during maintenance treatment. This was accompanied by a mean 7.1 ± 16.00 point improvement from Baseline in the Quality of Life Inventory in Epilepsy (QOLIE-31-P) total score for 24-week completers, with improvement reported in all subscales. Most common treatment-emergent adverse events (TEAEs) were dizziness (31.3%) and headache (13.5%). In the later add-on cohort, 39/261 (14.9%) and 29/249 (11.6%) patients remained seizure-free after completing 12 and 24 weeks' treatment, respectively. 178/353 (50.4%) patients achieved ≥50% reduction in seizure frequency during maintenance treatment. Mean change in QOLIE-31-P total score was 4.8 ± 14.74 points among 24-week completers. Common TEAEs were dizziness (33.6%), somnolence (15.0%) and headache (11.4%). Conclusions: Lacosamide initiated as first add-on treatment was efficacious and well tolerated in patients with uncontrolled POS.